The Comparison of Gait Kinematics in Over-Weight and Normal-Weight People across Age Groups - Mahdi Najafian Razavi (Biyumikānīk-i varzishī, 2022)
Objective Obesity and overweight have changed to very important factors in people movements in the modern world. Therefore, the present study was carried out to examine the effects of overweight on gait kinematic factors in children, young adults, middle-aged, and older adults. Methods The present study was a causal-comparative study in which 40 participants aged 9-85 were selected based on purposive sampling and were divided into eight groups (four normal groups and four overweight groups) based on body mass index (BMI). All the participants were healthy and had no physical abnormalities. The participants gait was normal.  The 3D motion analysis system was used for measuring gait parameters such as walking speed, stride length, stride width, single support phase duration, double support and swing phase duration. Two-way ANOVA was run for the purpose of data analysis.  SPSS 19 was used for statistical analyses at a significance level of p<0.05. Results Result showed that there was not significant differences between parameters of gait such as walking speed [age effect (0/364) and body position (0/478)], double support-phase duration [age effect (0/304) and body position (0/092)] and stance-phases duration [age effect (0/094) and body position (0/271)], while significant differences were observed in stride length [age effect (00001) and body position (0/038)], stride width [age effect (0/01) and body position (0/017)] and swing phase [age effect (0/0001) and body position (0/731)], between normal and overweight groups in different ages. The result of present study show that overweightness can affect some of the spatiotemporal parameters in people’s gait which can cause changes in the obese people’s gait pattern. Conclusion It seems that age and body status through height, weight and balance can affect some spatiotemporal parameters of gait.